Dari Trauma ke Tenang: Efektivitas Outdoor Healing terhadap Burnout Petugas Pendamping Kekerasan di Lhokseumawe - Idar Sri Afriyanti; Atika Rahmi Aw; Sinarsih Sinarsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Violence support workers are a professional group with a high vulnerability to burnout due to repeated exposure to victims’ traumatic experiences. Burnout among support workers not only affects individual mental health but also has implications for the quality of assistance and services provided to victims of violence. Therefore, effective intervention strategies are needed to reduce burnout in this population. This study aimed to examine the effectiveness of an outdoor healing intervention in reducing burnout levels among violence support workers. The study employed a quantitative approach with a one-group pretest–posttest design. A total of 20 violence support workers from Lhokseumawe and surrounding areas participated in the study and were selected using purposive sampling. Burnout levels were measured using the Maslach Burnout Inventory (MBI), which assesses emotional exhaustion, depersonalization, and reduced personal accomplishment. Data analysis was conducted using the Shapiro–Wilk normality test to ensure data distribution assumptions, followed by a paired sample t-test to examine differences in burnout scores before and after the intervention. The results showed a decrease in the mean burnout score from 56.20 at pretest to 53.75 at posttest. However, statistical analysis indicated that this reduction was not statistically significant (p = 0.278). These findings suggest that outdoor healing interventions may have potential as a supportive strategy for burnout recovery among violence support workers. Nevertheless, the results also indicate that a single or short-term outdoor healing intervention may not be sufficient to produce a significant reduction in burnout levels. Future research is recommended to implement interventions with longer duration, greater intensity, and more structured programs, as well as to employ more rigorous research designs to better evaluate the effectiveness of outdoor healing in reducing burnout among violence support workers.